The use of high-density autologous chondrocytes implant for the treatment of hip joint chondral defects - Raúl Torres-Eguia; Juan Manuel López-Alcorocho; Elena Rodríguez-Íñigo; Isabel Guillén-Vicente; Marta Guillén-Vicente; María Elena Díaz-Navarro; Lucía Áboli; Tomás F. Fernández-Jaén; Pedro Guillén-Garcia (Elsevier, 2022)
Introduction: In this work we describe the use of high-density autologous chondrocyte implantation (HD-ACI) to treat 2 patients with chondral defects in the hip. Case Presentation: Two male, 35- and 37-year-old, with chondral lesions and femoroacetabular impingement (FAI) were included. Chondrocytes were isolated expanded in vitro and then implanted at a density of 5 million cells per cm2 onto a type I/III porcine collagen membrane. None of the patients had surgery-derived complications. Pain disappeared in both cases at 6 months after surgery and was maintained until follow-up end (36 months). International Hip Outcome Tool (iHOT) score increased at 6 and 12 months and then leveled off until month 36.Three-year arthro-MRI showed the cartilage defects had been filled with a material similar to the surrounding healthy cartilage. Conclusion: HD-ACI is a safe and effective technique for focal cartilage lesion treatment in patients affected by evolved FAI.